2011
DOI: 10.1186/1752-4458-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Validation aspects of the health of the nation outcome scales

Abstract: BackgroundThe purpose of the current study was the psychometric evaluation of the Health of the Nation Outcome Scales (HoNOS), an instrument developed to meet the necessity of a clinically acceptable outcome scale for routine use in mental illness services.MethodsThe study participants included 2,162 outpatients and residential inpatients (rated on the HoNOS on three occasions during the year 2000) with a range of mental illnesses in different diagnostic groups from ten Mental Health Departments, located in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 32 publications
0
28
1
1
Order By: Relevance
“…The pseudo R 2 measure was used to estimate what part of the variance at practice level could be explained by including patient and general practice characteristics [25, 26]. For this, the percentages reduction in pseudo R 2 were calculated for each model compared to the empty model, expressing the part of the practice level variance that can be explained by the included characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…The pseudo R 2 measure was used to estimate what part of the variance at practice level could be explained by including patient and general practice characteristics [25, 26]. For this, the percentages reduction in pseudo R 2 were calculated for each model compared to the empty model, expressing the part of the practice level variance that can be explained by the included characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…These concerns are compounded by the lack of robust evidence from other studies for associations of HoNOS scores with costs,[1719,2123] operationalisation and validity issues [28,29], and the fact that the HoNOS were designed to measure clinical outcome rather than need for care. [49]…”
Section: Discussionmentioning
confidence: 99%
“…[28] Rasch analyses demonstrate the absence of an underlying construct in the composite scale. [26,29] Analyses involving individual HoNOS items have been undertaken in many studies. [16,17,30] There is no universal agreement regarding operationalisation of the HoNOS.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors indicated a four‐factor structure for the scale (Pirkis et al , ): 1) Behavior (items 1 to 3), Impairment (items 4 to 5), Symptoms (items 6 to 8), and Social (items 9 to 12). However, not all subsequent research has replicated this structure (Trauer, ; McClelland et al , ; Preston, ; Newnham et al , ; Lovaglio and Monzani, ) and, in Italy, Lovaglio and Monzani () proposed a six‐item one‐dimensional version for routine use in community‐oriented mental health services. The HoNOS‐6 demonstrated a solid factor structure (strong loadings and communalities), and acceptable model fit (Lovaglio and Monzani, ).…”
Section: Methodsmentioning
confidence: 99%